2022
DOI: 10.1002/ski2.167
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcome measures (PROMS) for body image in dermatology: A systematic review

Abstract: Introduction It is widely acknowledged that negative body image perception is linked to anxiety, depression, and body dysmorphic disorder. However, there is no gold standard, body image related patient reported outcome measure in use, specific for dermatologic disease, despite evidence to suggest a high prevalence of mental health problems relating to body image in this group of patients. Aim The aim of this study was to perform a review of body image Patient Reported Outcome Measures (PROMs) used in dermatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…To our knowledge, among the current PROMIS measures, there are no existing measures that capture body image or appearance. In addition, a systematic review of PROMs evaluating body image in dermatology found a small number of available PROMs investigating body image in dermatology and few with thorough evaluation of their content validity and measurement properties . Thus, there may be an unmet need for an adequately developed and validated measure to evaluate body image among patients with skin disease.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, among the current PROMIS measures, there are no existing measures that capture body image or appearance. In addition, a systematic review of PROMs evaluating body image in dermatology found a small number of available PROMs investigating body image in dermatology and few with thorough evaluation of their content validity and measurement properties . Thus, there may be an unmet need for an adequately developed and validated measure to evaluate body image among patients with skin disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this special edition of Skin Health and Disease we aim to showcase the breadth and depth of psychodermatology research, covering genetic and acquired skin diseases, involving patients across the entire age spectrum suffering from primary skin or psychiatric diagnoses. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Furthermore, we report the potential of medications to trigger autoimmune blistering disease in patients with neuropsychological disorders. 6 The issue also includes robust prospective epidemiological data from national registries examining associations between mental health and psoriatic arthritis in patients with psoriasis as well as charting the development of psychodermatology clinics and liaison services 7 and the establishment of patient reported outcomes measures for body image in dermatology is detailed.…”
mentioning
confidence: 90%
“…6 The issue also includes robust prospective epidemiological data from national registries examining associations between mental health and psoriatic arthritis in patients with psoriasis as well as charting the development of psychodermatology clinics and liaison services 7 and the establishment of patient reported outcomes measures for body image in dermatology is detailed. 8 Finally, Frewen et al show how psychodermatology can even get under the skin of healthcare professionals. 9 Specialised, multi-disciplinary clinics seem best placed to meet the growing need for psychodermatological service provision.…”
mentioning
confidence: 99%
See 2 more Smart Citations